PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA DAN INTENSI KELUAR PADA ASISTEN KURSUS METODE KUMON DI BALI DAN LOMBOK - Ananto, Setyo; Rahyuda, Ketut; Priartrini, Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aims to explain the effect of motivation on job satisfaction and turnover intention of the assistant Kumon class in Bali and Lombok. The population of the study are 347 people, consist of the assistant of the 40 classes in Bali and Lombok so by using probability sampling method and the slovin formula, respondents of this study are 78 people. The used of analytical methods is path analysis. The results of this study indicate that 1) the motivation has positive and significant impact on job satisfaction, 2) job satisfaction significantly and negatively related to the turnover intention, 3) motivation has significant negative effect to the turnover intention, and 4) motivation has significant negative effect to the turnover intention through job satisfaction.
Keywords: Motivation, Job Satisfaction, Turnover Intention